A Preliminary Desk Review of Urban Poverty in the East Asia Region : With Particular Focus on Indonesia, the Philippines, and Vietnam, Volume 1. Main Report - World Bank (Washington, DC, 2013)
This study reviews the available quantitative and qualitative information on urban poverty issues and trends in the East Asia and Pacific (EAP) Region, with particular focus on Indonesia, the Philippines, and Vietnam. The review is a desk study-which is limited to material accessible to the Bank in Washington and draws mainly on existing field work and other published and unpublished papers. The empirical analysis focuses on the household poverty surveys and World Bank-sponsored poverty assessments, which are the main data sources used by the World Bank and by the national governments in designing poverty-related activities. The three countries were chosen because each of them has had a recent Bank-assisted poverty assessment exercise, and an active dialogue with the Bank on urban strategy and operations. The report identifies certain shortcomings and gaps in the conventional poverty measurement approaches, and recommends refinements and priorities for further work. The Annex Tables contain detailed data from the national household surveys for Indonesia, the Philippines and Vietnam as described in the main text.